DETERMINAN KUALITAS AUDIT DI INDONESIA - Paradisa Sukma; Novia Rizki; Victoria Kusumaningtyas Priyambodo (Jurnal Ilmiah Akuntansi Indonesia, 2023)
This study aims to examine the effect of audit committee effectiveness and auditor characteristics on audit quality in manufacturing companies in Indonesia for the 2014-2018 period. The number of observations used was 615 observations. Hypothesis testing uses multiple linear regression models with ordinary least square (OLS) estimation. The results of the F test show that the effectiveness of the audit committee and the characteristics of the auditors significantly affect audit quality. The adjusted R square value of 25% indicates that there are other variables effect the model by 75%. The results of this study indicate that the effectiveness of the audit committee and specialized industry auditors have a significant positive effect on audit quality. An effective audit committee is formed based on three attributes, namely: the number of members, audit committee meetings, and expertise. Those attributes will be able to carry out a monitoring role to ensure that the financial information submitted by the company has shown the actual condition of the company so that the quality of the audit produced by KAP will increase. Likewise, the use of industry-specialized auditors by companies will improve audit quality through auditors' knowledge and experience in the industry.